An Analysis on The Use of Slang in Mean Girls Movie: Key words: Sociolinguistics, language, and slang - Oktaviani, Ni Wayan; singkoh, Olga; olii, Sanerita T. (Program Studi Pendidikan Bahasa Inggris, 2024)
The goal of the study is to identify the different slang terms that the performers in the Signify Girls movie used as well as explain what such terms mean. This study's research strategy might be characterized as a setting for gathering and analyzing information from the Mean Girls movie. The writer has the correct solution for analyzing the issue in the Mean Girls movie when employing qualitative research in place of descriptive data such as written and spoken. This study used the Eric Partridge theory to classify the slang terms that the actors in the Mean Girls movie used the most, and the Holmes (2013) theory of social factors that are the conversation's subject, setting, and participants' social relationships was used to analyze the context of the words used. The total number of words gleaned from the Mean Girls movie, including phrases, is 7. The top seven slang phrases used by actors are all listed here. Of the seven slang terms, three are classified as